Acupuncture at points LI4 and SP6 on Postpartum Sectio Caesarea (SC) Pain: Akupunktur pada titik LI4 dan SP6 pada Nyeri Postpartum Sectio Caeasarea (SC) - Nurul Azizah; Rafhani Rosyidah; Jamilahtur Rohamah (Universitas Muhammadiyah Sidoarjo, 2023)
This study will look at the effect of acupuncture at LI4 and SP6 points on postpartum SC pain. The research design is a quasi experimental clinical non-equivalent pre-post test control group design. The total sample is 60 respondents consisting of the intervention and control groups. The instrument used was the PNRS pain scale by measuring the level of pain before and after the intervention was given. Bivariate analysis using Independent Sample t-Test. The results of the study stated that the average pain intensity score before acupuncture intervention using PNRS there was a decrease after acupuncture intervention at points LI4 and SP6 after acupuncture intervention at points LI4 and SP6 for 30 minutes, analysis p value 0.00 <0.05. Conclusion There is a significant effect after being given acupuncture intervention at points LI4 and SP6 on reducing pain intensity in postpartum SC. Highlights: The study examines the effect of acupuncture on postpartum SC pain using a quasi-experimental design with intervention and control groups (n=60). Acupuncture at LI4 and SP6 points significantly reduces pain intensity in postpartum SC, as measured by the PNRS pain scale. Bivariate analysis (Independent Sample t-Test) shows a significant decrease in pain intensity after 30 minutes of acupuncture intervention at LI4 and SP6 points. Keywords: Acupuncture, Postpartum SC pain, LI4, SP6, Pain intensity.